Magnetic-luminescent nanocomposite CoFe2O4@SiO2@Gd2O3 : Eu2O3 : synthesis, characterization, and engulfment by macrophages - Vasylenko, I.V.; Yakovenko, A.V.; Yefremenko, D.S.; Telegeeva, P.G.; Dybkov, M.V.; Telegeev, G.D. (Reports of the National Academy of Sciences of Ukraine, 2016)
Multifunctional magnetic-luminescent nanocomposite CoFe2O4@SiO2@Gd2O3 : Eu2O3 is synthesized by the co-precipitation of salts of europium(III) and gadolinium(III) on a magnetic core CoFe2O4@SiO2 with the further thermal decomposition. The structure, phase, and luminescence properties are studied, by using the transmission electron microscopy (TEM), X-ray diffraction, and photoluminescent spectroscopy. The composite is tested for the survival of J774 macrophages and its engulfment by phagocytosis, by using trypan blue and acridine orange, respectively. Composite nanoparticles are spheres with a mean diameter of 200 nm according to the TEM images. Characteristic intensive red photoluminescent bands of Eu3+ ions are observed. Gadolinium oxide is a necessary component to prevent the Eu3+ luminescence concentration quenching. Due to luminescent and ferromagnetic properties, high survival, and phagocytic index, such na no composites are attractive for theranostics, in particular, cancer diagnostics, treatment by local hyperthermia, and for targeted drug delivery.